2006
DOI: 10.1161/circulationaha.106.613349
|View full text |Cite
|
Sign up to set email alerts
|

Critical Time Window for Intra-Arrest Cooling With Cold Saline Flush in a Dog Model of Cardiopulmonary Resuscitation

Abstract: Background-Mild hypothermia improves outcome when induced after cardiac arrest in humans. Recent studies in both dogs and mice suggest that induction of mild hypothermia during cardiopulmonary resuscitation (CPR) greatly enhances its efficacy. In this study, we evaluate the time window for the beneficial effect of intra-arrest cooling in the setting of prolonged CPR in a clinically relevant large-animal model. Methods and Results-Seventeen dogs had ventricular fibrillation cardiac arrest no flow of 3 minutes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
124
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(126 citation statements)
references
References 35 publications
0
124
0
2
Order By: Relevance
“…The suggested time window is short, lasts a few hours and is directly adjacent to the OHCA. 1,20 Therefore, the early and rapid application of TMH with only a difference of, for instance, two hours can have significant effects on the prognosis post-OHCA. Although showing an effect of TMH overall, we could not confirm these results from animal studies in our retrospective study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The suggested time window is short, lasts a few hours and is directly adjacent to the OHCA. 1,20 Therefore, the early and rapid application of TMH with only a difference of, for instance, two hours can have significant effects on the prognosis post-OHCA. Although showing an effect of TMH overall, we could not confirm these results from animal studies in our retrospective study.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The poor prognosis is related to the associated hypoxic cerebral damage during circulation arrest. 5,6 Therapeutic mild hypothermia (TMH) is recommended by the current guidelines on the post-resuscitation care of comatose subjects post-OHCA from the International Liaison Committee on Resuscitation (ILCOR) and European Resuscitation Council (ERC) 7,8 TMH post-OHCA is usually performed in an intensive care unit (ICU) and improves neurological outcome and decreases mortality.…”
mentioning
confidence: 99%
“…Animal studies have shown that there exists a critical time window after cardiac arrest during which cooling should be initiated to achieve the beneficial effects of induced hypothermia Nozari et al 2006). Although the mean delay to target temperature in the study by the Hypothermia After Cardiac Arrest Study group was up to eight hours and improved outcome was still observed (HACA 2002), current recommendation is that hypothermia should be induced as soon as possible (Castrén et al 2009;ERC 2005).…”
Section: Timing Of Hypothermiamentioning
confidence: 99%
“…Preferably, the treatment should be initiated as soon as possible (ERC 2005;Safar and Kochanek 2002b) such as in the prehospital setting. Furthermore, reports from experimental studies 6 have suggested that delay to cooling diminishes the beneficial effects of induced hypothermia and that ideally cooling should occur already during resuscitation Nozari et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have demonstrated that hypothermia initiated during or immediately after ROSC is associated with better organ preservation and increased survival. 56,57 Recently, in 49 patients treated with MTH, early achievement of the target temperature was an independent factor for good outcome 58 (GOE V). However, larger trials are warranted to assess the advantage of early vs. late cooling in humans.…”
Section: When and For How Long?mentioning
confidence: 99%